Gripped by 'Beauty contest syndrome' - New Sunday Times, Koh Aik Khoon (2009)
Six prominent alumni of Universiti Kebangsaan Malaysia (UKM) were invited by their Alma mater to reminisce about their students days on May 18, the 39th anniversary of the institution.